Stationary Boulders Increase River Seismic Frequency via Turbulence - Ron Nativ; Jens M. Turowski; Jui‐Ming Chang; Niels Hovius; Ci‐Jian Yang; Wen‐Sheng Chen; Wen‐Yen Chang; Jonathan B. Laronne (Geophysical Research Letters)
Abstract Despite a century of research, turbulent flows mobilizing bedload remain elusive, while seismic waves generated by surface processes can unravel river dynamics. We studied the seismic signals emitted near rivers in two tributaries characterized by large boulders. Data show an unusually high dominant seismic frequency, reaching >2 times the frequency observed in nearby smoother channels. Consistent high‐frequency content during periods without bedload transport prompts the hypothesis that turbulence is a key contributor to generating higher frequencies. Assuming that dominant turbulent eddies decrease in size due to boulder‐constrained flow, we formulate a frequency scaling relationship that aligns well with field data. A positive relationship of the frequency with water depth breaks at bedload onset, indicating that dissipation of flow energy partitions between turbulence and bedload transport. Our study shows that seismic frequency captures contrasting bed morphologies in mountain streams, offering insights into flow‐roughness interactions.